Perbandingan Hukum Negara Indonesia dan Arab Saudi Mengenai Tindak Pidana Kekerasan Seksual - Sarah Nur Izzati; M. Yusuf; Hermanto Harun; Kurnia Saputri; Ahmad Husairi (Fakultas Hukum Universitas Islam Indonesia, 2024)
Sexual violence is one of the conventional criminal offenses that has become a topic of discussion in the community. In this issue, the Criminal Code regulations are the main reference point for legal practitioners to catch perpetrators of sexual violence crimes. The crime of sexual violence is regulated primarily in Law no. 12 of 2022 concerning Crimes of Sexual Violence and Article 6 of the Law on the Eradication of Violent Crimes in the Kingdom of Saudi Arabia. Based on this, the researcher seeks to compare and analyze more deeply the regulation of the crime of sexual violence in the laws of Indonesia and Saudi Arabia. So that the topic of the problem is known through comparative efforts made against the two countries to enforce the law against the problematics of the crime of sexual violence. This research uses normative juridical research methods, by examining various problems based on theories, concepts and legal norms that apply in the crime of sexual violence, using library research, and data collection techniques carried out through document studies, so that conclusions can be drawn. So that it can be concluded that the similarities of the two articles are about sexual crimes and there is an element of coercion where Indonesia and Saudi Arabia, have laws that regulate sexual violence as a criminal offense. The analysis of the difference issues is in the realm of (1) Cultural and Religious Context, (2) Sanctions and Punishment, (3) Eradication and Prevention, and (4) Legal System.